Local botanical knowledge of cacti in the semi-arid region of Paraíba, northeastern Brazil. - Carvalho, Thamires Kelly Nunes; Lucena, Camilla Marque de; Lima, José Ribamar Farias; Cruz, Denise Dias da; Lucena, Reinaldo Farias Paiva de (Ethnobotany Research and Applications, 2019)
Background: The semi-arid region of Brazil has different physiognomies characterized by caatinga vegetation, represented by several botanical families, such as the Cactaceae, which stands out economically due to its diverse utilities. This study was conducted in the rural community of Capivara, from 2012 to 2015. This community is located in the municipality of Solânea, in the ‘Agreste’ Mesoregion and ‘Curimataú Oriental’ Microregion, in the state of Paraíba, northeastern Brazil. Methods: A semi-structured questionnaire was applied to 101 informants, family breadwinners (44 men and 57 women). The questionnaire addressed questions about the knowledge of the use of Cactaceae species in the region. Results: Ten species belonging to five genera were recorded, among which, the ‘facheiro’ (Pilosocereus pachycladus F. Ritter subsp. pernambucoensis (F. Ritter) Zappi) was the most cited and had the highest number of uses. Species were classified into twelve use categories and eleven usable parts were recorded. Fodder was the most prominent category (386 citations). The knowledge of plant species that grow in association with cacti was also recorded (18 species). Conclusions: Farmers in the community of Capivara have great knowledge of local Cactaceae species. However, they mainly use these species as fodder resources, especially C. jamacaru and P. pachycladus. Keywords: Ethnobotany, Cacti, Caatinga, Traditional knowledge, Rural community.